Sosialisasi Bijak Dalam Penggunaan Media Digital Untuk Meningkatkan Literasi Media Di SD Negeri Tempak Kecamatan Candimulyo Magelang - Arifina, Anisa Setya; Shodiqin, Ahmad Zakial; Masyiari, Muhammad Ilza; Ariani, Nesa; Mustaqlillah, Rahmania; Fata, Siti Mudhi Khatul (Jurnal Pengabdian kepada Masyarakat Radisi, 2023)
Media literacy is intelligence or skill in using media, including vulnerable audiences, namely students at SD Negeri Tempak, Candimulyo District, Magelang. These skills are important for students so that they are smarter in using and filtering information from the main media, namely digital media. This socialization was carried out with the aim of increasing the younger generation's understanding of media literacy so that they can be wise in using the media. Considering that there is still a very low level of media literacy, especially digital media among vulnerable audiences, this activity targets children at SDN Tempak. The method used to achieve this goal is video based learning and games. The results of this socialization show that there is an increase in knowledge and understanding about wisely using digital media by students at SDN Tempak.